A composition of bractatin and neobractatin from the fruits of Garcinia bracteata induces apoptosis in throat cancer through the endoplasmic reticulum stress, mitochondrial apoptotic and Akt pathways. (September 2021) - Huang, Huiqi; Peng, Yu; Zhou, Tongxi; Zhou, Xiandong; Deng, Jingtong; Yang, Xinzhou; Yang, Guangzhong
Graphical abstract: Highlights: A composition of prenylxanthones (CPX) inhibited throat cancer cells proliferation. CPX induced mitochondrial-mediated apoptosis in vitro and in vivo . CPX induced apoptosis by activating endoplasmic reticulum stress in vitro and in vivo . CPX induced apoptosis via Akt/GSK-3β/Bad pathway inhibition in vitro and in vivo . Abstract: Throat cancer is a common head and neck malignant tumor with a relatively high mortality rate. Prenylxanthone, is the major bioactive substance isolated from the genus Garcinia with anti-cancer effects. However, the anti-tumor activity of Prenylxanthone and its molecular mechanism in throat cancer have not been reported yet. In this study, a composition of two prenylxanthones (CPX) from the fruits of Garcinia bracteata was obtained to evaluate its chemical composition, anti-throat cancer ability and underlying mechanism in vitro and in vivo . The data revealed that CPX, composed of bractatin and neobractatin, dose-dependently suppressed throat cancer cells Hep-2 and FaDu proliferation and apoptosis, and inhibited xenografts growth in nude mice without significant toxicity. Furthermore, CPX exerted anti-throat cancer effect by inducing apoptosis through endoplasmic reticulum (ER) stress, mitochondrial apoptotic and Akt pathways. All results suggested that CPX could be considered as a potential chemotherapeutic drug for throat cancer.